Quntum chemical calculations of the spectroscopy of core electrons - Asmuruf, Frans Augusthinus (2010)
The performance of X-ray spectroscopy techniques has been advanced by recent reviving in X-ray sources. These techniques that involve the excitation of core electrons can provide an atom specific probe of electronic structure and provide powerful analytical tools that are used in many fields of research. Theoretical calculations can often play an important role in the analysis and interpretation of experimental spectra. In this thesis, I report a recent developments in quantum chemical calculations of X-ray absorption spectra, focusing on the use of time-dependent density functional theory to study core excitations. The practical application of these calculations is illustrated with examples drawn from surface science,and the application of these methods to study X-ray emission spectroscopy is also explored.